Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
x3 = (-64) x 125
x3 = (-4)3 x 53
x3 = (-4 x 5)3
x = (-4) x 5
x = -20
(x2+1)(x-1)(x3+1) = 0
x2+1 > 0 vì x2 >0
x-1 = 0 => x = 1
x3 + 1 = 0 => x3 = -1 => x = -1
\(\left(-64\right).125=\left(-4^3.5^3\right)=\left(-20\right)^3=x^3\Rightarrow x_0+25=-20+25=5\)
2. GIẢI
Ta có : \(\left(-2a^{ }\right)^3\).\(\left(3b^{ }\right)^2\)
Thay a=-1;b=-3 ta được:
\(\left[\left(-2\right).\left(-1\right)\right]^3\).\(\left[3.\left(-3\right)\right]^2\)=\(2^3.\left(-9\right)^2\)=\(8.81\)=\(648\)
1. GIẢI
Ta có : (x-1)(x+2)=0
=>\(\orbr{\begin{cases}x-1=0\\x+2=0\end{cases}}\)=>\(\orbr{\begin{cases}x=0+1\\x=0-2\end{cases}}\)=>\(\orbr{\begin{cases}x=1\\x=-2\end{cases}}\)
Vậy \(x\in\){-2;1}
Ta có 64=4^3
=> x+1=4
=>x=3
(x+1)3=43
x+1=4
x=3